Factors Predicting Successful Discontinuation of Continuous Renal Replacement Therapy. Issue 4 (July 2016) - Katayama, S.; Uchino, S.; Uji, M.; Ohnuma, T.; Namba, Y.; Kawarazaki, H.; Toki, N.; Takeda, K.; Yasuda, H.; Izawa, J.; Tokuhira, N.; Nagata, I.; et al.
This multicentre, retrospective observational study was conducted from January 2010 to December 2010 to determine the optimal time for discontinuing continuous renal replacement therapy (CRRT) by evaluating factors predictive of successful discontinuation in patients with acute kidney injury. Analysis was performed for patients after CRRT was discontinued because of renal function recovery. Patients were divided into two groups according to the success or failure of CRRT discontinuation. In multivariate logistic regression analysis, urine output at discontinuation, creatinine level and CRRT duration were found to be significant variables (area under the receiver operating characteristic curve for urine output, 0.814). In conclusion, we found that higher urine output, lower creatinine and shorter CRRT duration were significant factors to predict successful discontinuation of CRRT.